EVALUATION MANAGEMENT THROUGH EDM APPLICATION IN PREPARING e-RKAM - TAUFIQUR RAHMAN; Ifadhah, Hurriyatul; EVA ZAKIYATUL FAKHIROH; ALI NUR HADI (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2024)
The EDM and e-RKAM applications are key components of the Madrasah Reform Program. This initiative, launched by the Directorate General of Islamic Education with support from the World Bank, aims to enhance the quality and accountability of madrasa education. Through these applications, madrasas can improve evaluation management processes, ensuring transparency and effectiveness in budget planning and implementation. This study aims to analyze how EDM is applied in the preparation of e-RKAM, specifically in the stages of planning, organizing, implementing, and controlling at MIS Tarbiyatul Ulum Pamekasan. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation, verified using credibility, transferability, dependability, and confirmability tests. The findings highlight that RKAM is prepared annually with a student-centered approach. The head of the madrasa organizes a Quality Assurance Team, assigning specific roles to ensure smooth execution. During implementation, the EDM process aligns with e-RKAM instruments, facilitating comprehensive evaluation. Moreover, the control mechanisms are notably effective, with 100% budget realization across all programs. This showcases the significant role of EDM and e-RKAM in promoting efficient resource utilization and improving madrasa management quality. Keywords: Evaluation Management; EDM; e-RKAM; Madrasah Reform. Abstrak Aplikasi EDM dan e-RKAM merupakan komponen utama Program Reformasi Madrasah. Inisiatif yang diluncurkan oleh Direktorat Jenderal Pendidikan Islam dengan dukungan Bank Dunia ini bertujuan untuk meningkatkan mutu dan akuntabilitas pendidikan madrasah. Melalui aplikasi ini, madrasah dapat meningkatkan proses manajemen evaluasi, memastikan transparansi dan efektivitas dalam perencanaan dan pelaksanaan anggaran. Penelitian ini bertujuan untuk menganalisis bagaimana EDM diterapkan dalam penyusunan e-RKAM, khususnya pada tahap perencanaan, pengorganisasian, pelaksanaan, dan pengendalian di MIS Tarbiyatul Ulum Pamekasan. Dengan menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui wawancara, observasi, dan dokumentasi, diverifikasi menggunakan uji kredibilitas, transferabilitas, ketergantungan, dan konfirmabilitas. Temuan penelitian ini menyoroti bahwa RKAM disiapkan setiap tahun dengan pendekatan yang berpusat pada siswa. Kepala madrasah mengorganisasikan Tim Penjaminan Mutu, yang menugaskan peran khusus untuk memastikan pelaksanaan yang lancar. Selama pelaksanaan, proses EDM selaras dengan instrumen e-RKAM, yang memfasilitasi evaluasi yang komprehensif. Selain itu, mekanisme kontrolnya juga sangat efektif, dengan realisasi anggaran 100% di semua program. Hal ini menunjukkan peran penting EDM dan e-RKAM dalam mendorong pemanfaatan sumber daya secara efisien dan meningkatkan kualitas manajemen madrasah. Kata kunci: Manajemen Evaluasi; EDM; e-RKAM; Reformasi Madrasah.